Building healthy cities: the instrumentalization of intersectoral public health policies from Situational Strategic Planning - Lima, Filipe Antunes [UNESP]; Lima, Samuel do Carmo (Univ Sao Paulo, Fac Saude Publica, 2020)
The concern with living conditions in cities is not new and goes back to the proposals of utopian cities in ancient Greece, the Renaissance and the times of the industrial revolution of the 19th century. Modernist hygienist movements already proposed the need to build healthy cities. Since then. there is a vast literature dealing with the topic, with different epistemologies and approaches to the complex issue of urban health. Over the past 40 years, much has been advanced, not only in theory, in the design of healthy cities, but also in the experiences of the European Healthy Cities Network. There were occasional experiences in Brazil, but these did not develop in such a way as to become public policies. concrete. There is a need to plan coordinated and intersectoral health actions in all polices. It is necessary that there is participation and social control for healthy cities, and for this reason, this paper presents the Situational Strategic Planning as a methodology for building healthy cities. From the definition of the problem, the situational assessment. the elaboration of the plan until the evaluation, all these planning phases can strengthen public health policies and implement a national policy for healthy Brazilian cities.
Keywords: Healthy Cities; Public Policies; Strategic Planidng; Intersectoriality